Policy Framework Paper on Business Licensing Reform and Simplification - International Finance Corporation; Multilateral Investment Guarantee Agency; World Bank (Washington, DC, 2017)
This paper includes an overall introduction to the uses (and abuses) of business licenses, and to the way business licensing reforms can be organized. It also provides a broad overview and framework for licensing reforms. This paper is supported by more detailed case studies of licensing reform in particular sectors, and other guidance for facilities and field operations. This includes a detailed manual on 'how to' review and reform licenses and also information about how to apply effective and insightful Monitoring and Evaluation (M&E) to licensing reviews and reforms. Part one of this paper provides a contextual overview of key issues associated with government regulation. The rationale for government regulation (including licensing) is discussed, along with a description of the benefits and features of good regulatory design. Part two discusses the features of business licenses, the potential advantages and disadvantages of licensing and a discussion of the use of licensing fees and charges. Part three provides an overview of 'how to' reform business licenses and licensing systems. It summarizes broad approaches to reform, such as using a comprehensive 'top-down' approach to reviewing the stock of existing licenses, or where appropriate using a more targeted approach which focuses on particular types or categories of licenses. Part four of this paper focuses on M&E of licensing reform and simplification programs. This includes developing an M&E framework and measuring the significance and effects (e.g., the frequency and administrative burdens) generated by different types of licenses.